Calcium/Calmodulin-Dependent Kinase II Inhibition in Smooth Muscle Reduces Angiotensin II–Induced Hypertension by Controlling Aortic Remodeling and Baroreceptor Function - Prasad, Anand M (J Am Heart Assoc, 2015)
BACKGROUND: Multifunctional calcium/calmodulin-dependent kinase II (CaMKII) is activated by angiotensin II (Ang II) in cultured vascular smooth muscle cells (VSMCs), but its function in experimental hypertension has not been explored. The aim of this study was to determine the impact of CaMKII inhibition selectively in VSMCs on Ang II hypertension. METHODS AND RESULTS: Transgenic expression of a CaMKII peptide inhibitor in VSMCs (TG SM-CaMKIIN model) reduced the blood pressure response to chronic Ang II infusion. The aortic depressor nerve activity was reset in hypertensive versus normotensive wild-type animals but not in TG SM-CaMKIIN mice, suggesting that changes in baroreceptor activity account for the blood pressure difference between genotypes. Accordingly, aortic pulse wave velocity, a measure of arterial wall stiffness and a determinant of baroreceptor activity, increased in hypertensive versus normotensive wild-type animals but did not change in TG SM-CaMKIIN mice. Moreover, examination of blood pressure and heart rate under ganglionic blockade revealed that VSMC CaMKII inhibition abolished the augmented efferent sympathetic outflow and renal and splanchnic nerve activity in Ang II hypertension. Consequently, we hypothesized that VSMC CaMKII controls baroreceptor activity by modifying arterial wall remodeling in Ang II hypertension. Gene expression analysis in aortas from normotensive and Ang II–infused mice revealed that TG SM-CaMKIIN aortas were protected from Ang II–induced upregulation of genes that control extracellular matrix production, including collagen. VSMC CaMKII inhibition also strongly altered the expression of muscle contractile genes under Ang II. CONCLUSIONS: CaMKII in VSMCs regulates blood pressure under Ang II hypertension by controlling structural gene expression, wall stiffness, and baroreceptor activity.